Influence of Dietary Diversity and Its Associated Factors Among Human Immunodeficiency Virus–Infected Adult Patients Receiving Antiretroviral Therapy in Northwest Ethiopia - Yihenew Sewale; Kassahun Dires Ayenew (AIDS Research and Treatment)
Conclusions: The study found that nearly half of HIV-infected adult patients had an undiversified diet. Occupation being housewives and drivers, educational status of unable to write and read, WHO advanced HIV stage III and IV, and family size of 4–6 were statically significant factors associated with undiversified diet. We strongly recommend that policymakers, researchers, and nongovernmental organizations collaborate to implement holistic nutritional interventions to address dietary challenges and improve the overall health of people living with HIV/AIDS.